Observation of new states decaying into Λc+π-π+ - Artuso, M; Ayad, R; Boulahouache, C; Bukin, K; Dambasuren, E; Karamov, S; Majumder, G; Moneti, G; Mountain, R; Schuh, S; Skwarnicki, T; Stone, S; et al. (2001)
The spectrum of charmed baryons consisting of a charmed quark and two light quarks denoted by Ac and σc baryons were investigated. The sample used in the investigation corresponds to an integrated luminosity 13.7/fb from the data taken on the Y(4S) resonance and in the continuum at energies just below the Y(4S). A broad state with an invariant mass roughly above 480 MeV above that of the Ac baryon and a narrow state with an invariant mass of 596 MeV above the Ac mass were found.